2008
DOI: 10.1590/s0100-736x2008001000007
|View full text |Cite
|
Sign up to set email alerts
|

Comparação genotípica de isolados de Corynebacterium pseudotuberculosis de caprinos e ovinos do sertão de Pernambuco

Abstract: Objetivou-se com este estudo comparar genotipicamente 35 isolados de Corynebacterium pseudotuberculosis recuperados de conteúdo de abscessos de caprinos e ovinos com linfadenite caseosa, procedentes de cinco municípios localizados no Sertão de Pernambuco, Brasil. Utilizou-se a técnica de fingerprint RFLP-PCR com as enzimas de restrição Hpy-Ch4 e Msp1 aplicada ao gene rpoB e as enzimas Pst I e Msp I para o gene pld. Não houve diferença nos padrões de fragmentos de bandas entre os isolados, independente da espéc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
3
8
1
8
Order By: Relevance
“…The same repeats with penicillin, drug with higher percentage of resistance of the tested strains. Corroborating with previous studies with bacteria of the genus Corynebacterium (Abreu et al, 2008), Staphylococcus (Moreira et al, 2010) and E. coli (Baccaro, 2002).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The same repeats with penicillin, drug with higher percentage of resistance of the tested strains. Corroborating with previous studies with bacteria of the genus Corynebacterium (Abreu et al, 2008), Staphylococcus (Moreira et al, 2010) and E. coli (Baccaro, 2002).…”
Section: Discussionsupporting
confidence: 83%
“…Although the bacterial resistance configures a problem in population often submitted to antibiotic therapy (Baccaro et al, 2002), this reality has also been related in wild birds (Santos et al, 2010), corroborating this study, in which the strains isolated from Magellanic penguins without previous antibiotics treatment presented varied susceptibility facing the tested antimicrobial. Therefore, using the data obtained in this study, enrofloxacin and cephalosporin may be indicated in empiric bumblefoot treatment, while the use of penicillin and streptomycin is not indicated, since drugs with more than 20% of local resistance are not recommended for empirical treatment (Naber, 2000).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…A linfadenite caseosa ϐigura dentre as afecções mais frequentes na criação de pequenos ruminantes no Brasil (Dorella et al 2006, Abreu et al 2008, Carvalho et al 2008. A doença se caracteriza pela formação de abscessos em linfonodos, causada predominantemente por Corynebacterium pseudotuberculosis (Dorella et al 2006).…”
Section: Discussão E Conclusõesunclassified